Membentuk Karakter Peserta Didik Melalui Pembelajaran Matematika Realistik di Madrasah Ibtidaiyah (MI) - Fatmahanik, Ulum (IAIN Ponorogo, 2016)
Measure of success of an education is not only seen from the success of cognitive terms but also in terms of the successful cultivation of the values of character. Mathematics become part of the curriculum in Indonesia and has a very important role in every level of education. So that learning mathematics is expected to make an important contribution in shaping the character of students. Learning mathematics should be designed either by inserting the values of the characters in the learning plan so that the purpose of forming the character of students can be achieved. In this paper the authors will examine one example of mathematics learning with learning approach realistic mathematics, the principles, characteristics and stages is expected capable sculpt the character of learners such as responsibility, hard working, honest, independent, creative, curious, tolerance, mutual respect, democratic and friendly or communicative ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© ØªÙØ¶ÙØ Ø§ÙØÙÙÙØ© Ø£Ù ÙØ¬Ø§Ø Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ ÙÙÙØ§Ø³ Ø¨Ù ÙÙØ§Ø³ Ø§ÙÙØ¬Ø§Ø ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙÙ Ø¹Ø±ÙÙ ÙØØ³Ø¨ Ø¨Ù ÙÙÙÙ Ø§ÙÙØ¬Ø§Ø ÙØ°ÙÙ ÙÙ ØºØ±Ø³ Ø§ÙÙÙÙ Ø§ÙØ£Ø®ÙØ§ÙÙØ© ÙØ§ÙØ´Ø®ØµÙØ©. Ø£ØµØ¨Ø Ø¹ÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª Ø£ØØ¯ Ø§ÙÙ ÙØ§Ø¯ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ ÙÙÙ Ø¯ÙØ± ÙØ¹ÙØ§Ù ÙÙ Ø¬Ù ÙØ¹ Ø§ÙÙ Ø±Ø§ØÙ Ø§ÙØ¯Ø±Ø§Ø³ÙØ© ØØªÙÙ ÙÙÙÙ ØªØ¯Ø±ÙØ³ Ø¹ÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙ Ø§Ø³ÙØ§Ù ÙÙ ØªÙÙÙÙ Ø´Ø®ØµÙØ© Ø§ÙØ·ÙØ§Ø¨. ÙØ°Ø§ ÙØ¥ÙÙ ÙØ§Ø¨Ø¯ Ù Ù Ø¥Ø¹Ø¯Ø§Ø¯ ØªØ¯Ø±ÙØ³ Ø¹ÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª Ø¨Ø£ØØ³Ù Ù Ø§ Ø£Ù ÙÙ Ø¨ØªÙ Ø²ÙØ¬ Ø§ÙÙÙÙ Ø§ÙØ´Ø®ØµÙØ© ÙÙ ÙØ°Ø§ Ø§ÙØ¥Ø¹Ø¯Ø§Ø¯ ØØªÙ ÙØªÙ Ù ØªÙÙÙÙ Ø´Ø®ØµÙØ© Ø§ÙØ·ÙØ§Ø¨. ÙØ£ØØ¯ Ù Ø¯Ø§Ø®Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙ ÙØ§Ø³Ø¨ ÙØªÙÙÙÙ Ø´Ø®ØµÙØ© Ø§ÙØ·ÙØ§Ø¨ ÙÙ ØªØ¹ÙÙÙ Ø¹ÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª Ø¨Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙØ§ÙØ¹Ù. ÙØ¬Ø ÙØ°Ø§ Ø§ÙÙ Ø¯Ø®Ù ÙÙ ØªÙÙÙÙ Ø´Ø®ØµÙØ© Ø§ÙØ·ÙØ§Ø¨ ÙÙ ØµÙØ§Øª : Ø§ÙÙ Ø³Ø¤ÙÙÙØ©Â ÙØ§ÙØ¬Ø¯ÙÙØ© ÙÙ Ø§ÙØ¹Ù ÙØ ÙØ§ÙØµØ¯ÙØ ÙØ§ÙØ¥Ø¨Ø¯Ø§Ø¹ÙØ©Ø ÙØ§ÙØ¥Ø¹ØªÙ Ø§Ø¯ Ø¹ÙÙ Ø§ÙÙÙØ³Ø ÙØ§ÙØØ±Øµ Ø¹ÙÙ Ø§ÙÙ Ø¹Ø±ÙØ©Ø ÙØ§ÙØªØ³Ø§Ù ØØ ÙØ§ØØªØ±Ø§Ù Ø§ÙØºÙØ±Ø ÙØ§ÙØ¯ÙÙ ÙØ±Ø§Ø·ÙØ©Ø ÙØ§ÙØ±ØÙ Ø©Ø ÙØ§ÙØªÙØ§ØµÙ Ø§ÙÙ ÙØ§Ø³Ø¨Ø© Ø¨Ø§ÙÙÙÙ Ø§ÙØ´Ø®ØµÙØ© Ø§ÙÙ Ø³ØªÙ Ø¯Ø© Ù Ù Ø§ÙØªØ¹Ø§ÙÙÙ Ø§ÙØ¯ÙÙÙØ©Ø ÙØ§ÙØ¨ÙØ¬Ø§Ø³ÙÙØ§Ø ÙØ§ÙØ«ÙØ§ÙØ© ÙØ§ÙØ£ÙØ¯Ø§Ù Ù Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙØ·ÙÙØ©